Fog at Hillingdon - Langford, David K., 1942- (Book collections on Project MUSE., 2015)
While fog does not come easily or frequently to Central Texas, when it does, it inspires moments of quiet and reflection. David K. Langford captures those moments here in stirring images of the comings and goings of fog on Hillingdon Ranch, family land that has benefited from the stewardship of six generations. These photographs in turn inspired an essay by writer Rick Bass that takes him back to his own memories of fog-in the Texas Hill Country and elsewhere. Fog at Hillingdon includes a personal note by Langford on his techniques and camera equipment. Apt historic or contemporary quotations s.